2012
DOI: 10.1088/0031-8949/86/01/018403
|View full text |Cite
|
Sign up to set email alerts
|

Vortex tubes of turbulent solar convection

Abstract: Abstract. Investigation of the turbulent properties of solar convection is extremely important for understanding the multi-scale dynamics observed on the solar surface. In particular, recent high-resolution observations have revealed ubiquitous vortical structures, and numerical simulations have demonstrated links between vortex tube dynamics and magnetic field organization and have shown the importance of vortex tube interactions in the mechanisms of acoustic wave excitation on the Sun. In this paper we inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…The strongest vertical vortices are detected on small granules. This is in accordance with findings in Kitiashvili et al (2012) where vertical vortex tubes were found to be formed inside granules as a result of the local instability caused by small upflowing plumes. In the scatter plot, two concentrations of vertical vortices are visible at the location of granules with 700 km and 1400 km in diameter, further supporting the idea of the existence of two populations of granules.…”
Section: Discussionsupporting
confidence: 93%
“…The strongest vertical vortices are detected on small granules. This is in accordance with findings in Kitiashvili et al (2012) where vertical vortex tubes were found to be formed inside granules as a result of the local instability caused by small upflowing plumes. In the scatter plot, two concentrations of vertical vortices are visible at the location of granules with 700 km and 1400 km in diameter, further supporting the idea of the existence of two populations of granules.…”
Section: Discussionsupporting
confidence: 93%
“…Small-scale vortices in the quiet Sun regions are widely accepted to form due to turbulent convection and the bathtub effect (e.g. Shelyag et al 2011;Kitiashvili et al 2012a;Shelyag et al 2012). Solar photospheric vortex flows have drawn the attention of researchers as they have the potential to excite a wide range of MHD waves, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Granular-scale vortical flows in quiet Sun regions are thought to be generated mainly by turbulent convection in subsurface layers of the Sun and its interaction with the solar atmosphere (e.g., Stein & Nordlund 2000;Kitiashvili et al 2012a). These smallscale vortical flows have caught significant attention in relation to the formation of magnetic or nonmagnetic vortex tubes (e.g., Moll et al 2011;Shelyag et al 2011;Kitiashvili et al 2012b), the formation of acoustic/Alfvén/shock waves (e.g., Fedun et al 2011;Kitiashvili et al 2011), and the heating of the upper solar atmosphere (e.g., Sturrock & Uchida 1981;Zirker 1993).…”
Section: Introductionmentioning
confidence: 99%